Identificação de leveduras isoladas da rizosfera de Alternanthera philoxeroides (Mart.) Griseb e avaliação do seu potencial de degradação de petróleo - Santos, Jéssica Janzen dos (2017)
Petroleum is currently the world's main energy source, and its demand is expected to increase in the coming years. Likewise, accidents such as accidental spills, leaks and liabilities arising from the refining of oil grow at the same rate and cause contamination of terrestrial and aquatic ecosystems, and oil may persist for long periods in the environment. Faced with these facts, it is necessary to treat and develop techniques that can reduce or even eliminate contaminants. Among the treatment techniques, bioremediation stands out as being a simple, efficient, low-cost and less aggressive method when compared to commonly used techniques. It is characterized by the use of microorganisms that have the ability to degrade, eliminate or transform pollutants present in the environment into compounds, often less toxic. These microorganisms can be selected from the roots of phytoremediation plants which, in the case of petroleum, provide favorable conditions for their growth, increasing aeration and, consequently, the biodegradation of contaminants, a process known as rhizodegradation. Thus, the present research had as objective to make the molecular identification by nucleotide sequencing and amplification by DNA polymerase chain reaction (PCR) two yeasts isolated from the rhizosphere of Alternanthera philoxeroides (Mart.) Griseb., and to carry out individual tests for evaluate the potential for the degradation of petroleum hydrocarbons for bioprospecting and biotechnological application. The cultivations were performed in mineral medium plus petroleum as the only source of carbon, under different time intervals (0, 24, 48, 72 and 96h). The parameters of temperature, hydrogenation potential (pH), electrical conductivity (EC), absorbance at 610 nm by optical density (OD) were analyzed, as well as the hydrocarbon profile by gas chromatography (GC). Yeasts previously labeled as L1 morphotype and L2 morphotype were identified as: Rhodotorula glutinis and Sporidiobolus pararoseus, respectively. The results of the individual oil degradation test with R. glutinis revealed 24h time biomass growth with a degradation percentage of 59.57, 72.34, 63.52, 68.94, 77.96, 78.99, 58.38, 68.43, 44.74, 61.49, 46.13 and 66.49% of the petroleum compounds. The result of the individual petroleum degradation test with S. pararoseus revealed that, although the OD showed that biomass growth occurred in 48h and 72h times, the chromatographic analysis showed that there was no degradation of the petroleum compounds. As a result of the present research, it is hoped to contribute to the problem not only of soil contaminated with oil, but of other environments affected by it. These results help fill the gap between the field of bioremediation and laboratory approaches by providing an insight into the processes of environmental recovery, as there are no papers in the literature that report the use of the microorganisms Rhodotorula glutinis and Sporidiobolus pararoseus for the degradation of petroleum.